Residential Area Characteristics Are Associated With Asthma Burden in Children - Erkkola, Riku; Gonzales‐Inca, Carlos; Vahtera, Jussi; Bergroth, Eija; Korppi, Matti; Camargo, Carlos A.; Jartti, Tuomas (Wiley, 2025)
Background
Wheezing illnesses, especially those triggered by rhinovirus infection, cause a major disease burden, and they often precede asthma. Environmental exposures are known to affect recurrence of wheezing. We investigated the relations of population density, greenness (forested areas), and socioeconomic factors of the living surroundings to the burden of asthma in children with prior bronchiolitis.
Methods
Three hundred and ninety-four children, aged 0–24 months, with doctor-diagnosed bronchiolitis were enrolled in the MARC-30 Finland study. We assessed the children's early-life exposures to greenness and socioeconomic factors using time-series of Corine Land Cover data and Statistics Finland's grid data. We compared the living surroundings data to the prescription drug purchases and special asthma reimbursement benefits until the age 8 years; asthma data were from the Social Insurance Institution of Finland.
Results
Children living in sparsely populated areas had lighter asthma disease burden than children living in densely populated ones, with burden measured in median bronchodilator (50DDD [defined daily dose] vs. 104DDD, p = 0.02) and inhaled corticosteroid (0DDD vs. 123DDD, p = 0.04) purchases. In the subgroup of children with rhinovirus-induced bronchiolitis, children living in more forested areas developed asthma 10 months later than those with less forested areas (p = 0.04). Neighborhood socioeconomic characteristics were not associated with differences in asthma burden.
Conclusions
Sparsely populated areas and forested environments seem to have a beneficial association with children's respiratory health. These findings warrant further studies on the protective health effects of greenness and the type of biodiversity around homes.